Vibrant Matter, Actants and the Limits of Human Agency in Saramago’s The Stone Raft - Catherine Macmıllan (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
This paper focuses on José Saramago’s novel The Stone Raft, set during an imaginary geo(il)logical event, the separation of the Iberian Peninsula from the European mainland. This event brings together a group of human and non-human protagonists, who seem to have mysterious connections with this event. The novel follows the group, which arguably forms a mini-community, as they travel around the former peninsula. It also explores the political disruptions which this event, directly and indirectly, provokes at various levels from the local to the international, including, for instance, closer relations between Portugal and Spain the souring of relations between the Iberian countries and Europe, widespread protests in Europe and the occupation of hotels by slum-dwellers across the Peninsula. In this context, the novel is explored from the perspective of Jane Bennett’s vital materialism, as put forward in her 2010 book “Vibrant Matter”. For Bennett, humans tend to overestimate their agency, while viewing matter as simply inert. In her view, however, material things may be important ‘actants’, particularly when they act as part of a human/non-human assemblage. Saramago’s narrator, like Bennett herself, constantly questions the human tendency to over-attribute agency (and responsibility) for events to humans alone, suggesting that matter, and human/non-human assemblages, may also be important actants.